Resilience of Teenagers of Orphanage in Adjustment and Facing The Reality of Life - Neviyarni Neviyarni; Netrawati Netrawati (Jurnal Neo Konseling, 2019)
The problem about resilience of teenagers of orphanage is an interesting topic done because various of changes physically, cognitively, psychologically, and social-culture happened in adolescence. In addition, the teenagers from orphanage are separated from their biological parents Then, they face problems with a lot of pressure of life during staying in orphanage and they have to be able to adapt with the situation and tough condition of the reality of life. They must survive and rise up from those difficult moments. One of their abilities needed to describe about is resiliency. The tendency of resilience from them is in an enough category at conforming, it is 44,19%. it is important to follow up from the orphanages’ founder to help them in increasing resilience and adjustment.